Islam Berkemajuan dan Pembentukan Karakter Anak Asuh di Lembaga Kesejahteraan Sosial Anak Amrullah Aisyiyah Limbung - Arifin, Ansar; Basir, Muhammad; Tahara, Tasrifin; Hadisaputra, Hadisaputra (Al Asma: Journal of Islamic Education, 2025)
This study aims to explore the role of Islamic orphanages (Lembaga Kesejahteraan Sosial Anak, LKSA) grounded in the values of Progressive Islam (Islam Berkemajuan) in shaping children’s character, leadership, and social engagement. Employing a qualitative approach, this research utilizes participatory observation and in-depth interviews conducted at the Amrullah Aisyiyah Orphanage in Limbung. Data were collected over a month period and analyzed using a thematic approach guided by the pedagogical framework of Progressive Islam. The findings reveal that daily religious routines within the orphanage play a fundamental role in instilling discipline and moral identity among children. Skills training programs, integrated with Islamic values, significantly contribute to fostering self-reliance and leadership capabilities. Moreover, the institution’s active involvement in non-resident child development illustrates its critical role in empowering the surrounding community. The Progressive Islam framework has proven to be an effective foundation for the holistic integration of spiritual, social, and vocational development. This research enriches the discourse on faith-based character education and highlights the potential of Islamic orphanages as agents of social transformation. The findings serve as a reference for designing educational policies and programs in LKSAs and provide a basis for further studies on the role of religious institutions in community development.